2009
DOI: 10.1002/ceat.200800343
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Primary Nanoparticle Agglomeration in Precipitation of Silver

Abstract: The precipitation kinetics of silver was studied using a lab-scale batch crystallizer with special attention to characterization of agglomeration of primary nanoparticles. The vessel was operated at different feed concentrations, molar ratios, and stirrer speed. Nucleation, volume average crystal growth rates, and agglomeration kernels were determined. Empirical relations were obtained between the rates of the different crystallization steps with supersaturation, magma density, and energy dissipation rate. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…The degree of aggregation of nanomaterials can be regulated via kinetic control, such as the degree of mechanical agitation of atomic agents. 31,32 We controlled stirring conditions with respect to the batch size to facilitate the aggregation of crystal seeds, which leads to the aggregation of primary nanoparticles into more extensive superstructures. Under weak agitation and weak shear flow, the primary nanowires aggregated via side-toside packing into superstructures that resulted in the formation of highly crystalline nanorod particles, which can be explained by the Ostwald ripening mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of aggregation of nanomaterials can be regulated via kinetic control, such as the degree of mechanical agitation of atomic agents. 31,32 We controlled stirring conditions with respect to the batch size to facilitate the aggregation of crystal seeds, which leads to the aggregation of primary nanoparticles into more extensive superstructures. Under weak agitation and weak shear flow, the primary nanowires aggregated via side-toside packing into superstructures that resulted in the formation of highly crystalline nanorod particles, which can be explained by the Ostwald ripening mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of the high stirring rate is to promote a better dispersion of the silver ions, favoring the catalyzed reduction of these ions onto the gold seeds at the surface of the silica nanoparticles. In reaction crystallization, ions cluster together to originate particles and these particles form agglomerates or aggregates . Gulrajani et al demonstrated that increasing the stirring rate leads to a decrease in particle size, indicating a better dispersion of colloidal elements which minimizes agglomeration .…”
Section: Results and Discussionmentioning
confidence: 99%